Application of Theory of Planned Behavior in Efforts to Increase Community Participation in Vaccination Programs (Study at the Covid-19 Vaccination Program, Pasirwangi District, Garut Regency) - Bangkara, BMAS Anaconda; Syuryadi , Matnur; Marwah, Hanny (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2023)
Abstract It should be grateful that the Covid-19 pandemic is getting under control; however, there are still problems related to community participation, especially in the vaccination program. Apart from the Covid-19 vaccination, in Indonesia there are still a number of other vaccinations that, really need the participation of the community. As happened in Pasirwangi District, Garut Regency, out of 53,093 residents who met the requirements to get the Covid-19 vaccine, only 2,492 residents, took advantage of this opportunity. For this reason, this study intends to find alternative ways, through the application of the theory of planned behavior, to increase opportunities for community participation by identifying which variables have the most potential to be used for this purpose. Efforts to collect data through the distribution of questionnaires with an alternative of 5-likert scale answers and involving 650 respondents through purposive sampling technique The analysis tool used was SEM AMOS. The results showed that all exogenous variables were significantly correlated with endogenous variables (behavior), as well as intervening variables that were significantly correlated with endogenous variables. Through the Sobel test, a review of indirect effects was also carried out, and the results showed that all indirect effects were significantly correlated with endogenous variables. Keywords: Vaccination, theory of planned behavior, society participation Abstrak. Patut disyukuri, pandemic Covid-19 semakin terkendali, namun demikian, masih terdapat persoalan berkaitan dengan partisipasi masyarakat, khususnya berkaitan dengan peran serta dalam program vaksinasi. Selain vaksinasi Covid-19, di Indonesia masih terdapat sejumlah vaksinasi lain yang tentunya sangat membutuhkan peran serta masyarakat. Seperti yang terjadi di Kecamatan Pasirwangi Kabupaten Garut, dari 53.093 penduduk yang memenuhi syarat untuk mendapatkan vaksin Covid-19, hanya 2.492 penduduk, atau sekitar 4,7% yang memanfaatkan kesempatan ini. Untuk itu, penelitian ini bermaksud untuk mencari alternative cara, agar peluang partisipasi masyarakat meningkat, melalui penerapan Theory of Planned Behavior, menemukenali variable manakah yang paling potensial dimanfaatkan untuk tujuan ini. Upaya pengumpulan daya melalui penyebaran kuesioner pernyataan tertutup, dengan alternative 5 jawaban berskala likert, dan melibatkan 650 responden, melalui teknik sampling purposive. Alat analisis yang digunakan adalah SEM AMOS versi 26. Hasil penelitian menunjukkan semua variable eksogen berkorelasi signifikan terhadap variable endogen (Behavior), juga variable intervening yang berkorelasi signifikan terhadap variable endogen. Melalui uji Sobel, dilakukan juga tinjauan indirect effect, dan hasilnya semua indirect effect berkorelasi signifikan terhadap variable endogen. Dengan demikian, berdasarkan variable yang ada di teori ini dapat dimanfaatkan bagi upaya peningkatan kesadaran masyarakat berpartisipasi aktif dalam program pemerintah, khususnya berkait dengan program vaksinasi yang tidak hanya untuk covid-19. Kata kunci: Vaksinasi, theory of planned behavior, partisipasi masyarakat